The elusive quest for supply response to cash-crop market reforms in sub-Saharan Africa: the case of cotton - (:unkn) unknown (My University, 2013)
Little cross-cutting conclusions emerge from comparative studies on the impact of structural adjustment on Sub-Saharan African agricultural performance. This paper aims to illuminate this long-standing debate by adopting a novel quantitative, sectoral and long-term approach controlling for country-specific determinants. It incorporates detailed information on the pace of reforms and the nature of post-reform market structure, pre-reform policies and weather conditions at the cultivation zone level. The cotton sector is the focus of this paper because of its particularly interesting institutional history. The authors find that the changes in market structure brought about by reforms have had very different impacts in Francophone West and Central Africa and in the rest of Sub-Saharan Africa. In the former region, production has been higher but productivity lower, on average, in regulated markets than in monopolistic markets. Conversely, in the liberalized markets of the rest of Sub-Saharan Africa, productivity has been higher in than in monopolistic markets but highly competitive markets seem to have produced less than monopolistic sectors.
Keywords: African Research